2018
DOI: 10.1111/wrr.12648
|View full text |Cite
|
Sign up to set email alerts
|

Losartan ointment relieves hypertrophic scars and keloid: A pilot study

Abstract: Keloid and hypertrophic scars are two types of fibrosis caused by extracellular matrix overexpression, and angiotensin II via AT receptor is known to play a key role in stimulation of fibrosis. A pilot placebo controlled single blind study was carried out on patients with hypertrophic scars and keloids. A total of 37 adult volunteers were randomly assigned into losartan 5% or placebo treatment groups. The treatment was performed twice a day for three months and a 6-month follow-up. The treatment was evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 13 publications
0
36
0
Order By: Relevance
“…56 Third, a randomized placebo-controlled study of 30 adult cutaneous pathological scar patients showed that twice-daily topical application of an ointment containing losartan (5%), which inhibits AT1R, significantly improved the Vancouver Scar Scale scores for both keloid and hypertrophic scar patients (P < .01). 57 Fourth, a case report showed a beneficial effect of captopril (an ACE inhibitor) on keloids: when an 18-year-old patient with keloids on her hand was treated topically with a 5% captopril solution in cold cream twice daily for 6 weeks, the height of the lesions dropped from 9-11 mm to 2-4 mm and there was an obvious improvement in the scaling and erythema. 58 The mechanisms underlying the keloidogenesis and keloid-aggravating effects of systemic hypertension remain to be fully elucidated but we speculate that it acts (i) by aggravating the endothelial dysfunction in cutaneous pathological scars 59 or (ii) by activating local RAS in the skin/pathological scar, thereby promoting the profibrotic activities of fibroblasts and driving local inflammation.…”
Section: Renin-angiotensin Systemmentioning
confidence: 99%
“…56 Third, a randomized placebo-controlled study of 30 adult cutaneous pathological scar patients showed that twice-daily topical application of an ointment containing losartan (5%), which inhibits AT1R, significantly improved the Vancouver Scar Scale scores for both keloid and hypertrophic scar patients (P < .01). 57 Fourth, a case report showed a beneficial effect of captopril (an ACE inhibitor) on keloids: when an 18-year-old patient with keloids on her hand was treated topically with a 5% captopril solution in cold cream twice daily for 6 weeks, the height of the lesions dropped from 9-11 mm to 2-4 mm and there was an obvious improvement in the scaling and erythema. 58 The mechanisms underlying the keloidogenesis and keloid-aggravating effects of systemic hypertension remain to be fully elucidated but we speculate that it acts (i) by aggravating the endothelial dysfunction in cutaneous pathological scars 59 or (ii) by activating local RAS in the skin/pathological scar, thereby promoting the profibrotic activities of fibroblasts and driving local inflammation.…”
Section: Renin-angiotensin Systemmentioning
confidence: 99%
“…Morihara et al (50) show significantly higher ACE activities in wounded skin and pathological scar tissue than in normal skin, implying increased levels of ATII in these conditions. Treatment with ATIIR 1 blockers significantly reduces the pliability and vascularity of KLs and hypertrophic scars (58). This observation along with improvement of KLs following treatment with lowdose enalapril, an ACE inhibitor, further supports the role of the RAS in KD (59) (Figure 2).…”
Section: Renin-angiotensin System and Keloid Disordermentioning
confidence: 60%
“…[37,39] To the best of our knowledge, so far, two studies have tested the treatment of hypertrophic scars and keloids in humans by topical application of formulations of the ACE inhibitor enalapril or the AT 1 R antagonist losartan in randomised, single-or double-blind clinical trials ( Table 1). [50,52] In the losartan study, patients with hypertrophic scars or keloids from different causes were treated for 3 months with a 5% losartan ointment (n = 20) or placebo (n = 10; 7 of originally 17 patients in this group terminated the study prematurely because of no treatment effect) and followed up for 6 months. [52] In the enalapril study, 30 patients with hypertrophic scars as result of 2nd or 3rd degree burns were treated for 6 months with a 1% enalapril ointment or placebo (subjects had two same-degree scars on symmetrical sites of body which were randomly allocated to the treatment or placebo groups).…”
Section: The Cutaneous Renin-angiotensin System In Hypertrophic Scamentioning
confidence: 99%
“…[50,52] In the losartan study, patients with hypertrophic scars or keloids from different causes were treated for 3 months with a 5% losartan ointment (n = 20) or placebo (n = 10; 7 of originally 17 patients in this group terminated the study prematurely because of no treatment effect) and followed up for 6 months. [52] In the enalapril study, 30 patients with hypertrophic scars as result of 2nd or 3rd degree burns were treated for 6 months with a 1% enalapril ointment or placebo (subjects had two same-degree scars on symmetrical sites of body which were randomly allocated to the treatment or placebo groups). [50] In both studies, at the end of the 6-month observation/treatment period, scars were significantly smaller when treated with losartan/enalapril than the placebo-treated scars.…”
Section: The Cutaneous Renin-angiotensin System In Hypertrophic Scamentioning
confidence: 99%